GE_GERICHTE P/16594/2017 vom 12. Juni 2018 - GE Cour de justice (2018)
LÉSION CORPORELLE PAR NÉGLIGENCE ; DILIGENCE ; TORT MORAL ; VIOLATION DES RÈGLES DE LA CIRCULATION | CP.125; CP.12.al3; CO.47; LCR.26; OCR.14